2013
DOI: 10.1371/journal.pone.0070887
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Bacteria Isolated from the Internal Organs of Edible Snow Crabs

Abstract: Antibiotic resistance and microbiota within edible snow crabs are important for the Chionoecetes (snow crab) fishing industry. We investigated these parameters using culture methods and antibiotic susceptibility tests with six internal organs from three species of Chionoecetes. Each sample revealed many unexpected microbial species within Chionoecetes internal organs. On the basis of 16S rRNA sequence analysis of 381 isolates, the most abundant genera identified in Chionoecetes opilio were Acinetobacter spp. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Isolates that showed an antimicrobial resistance phenotype were screened for the presence of genes coding for resistance determinants. The genes associated with resistance to B-lactams ( blaTEM, blaSHV, blaOXA ), tetracyclines ( tetA, tetB, tetC, tetG ), chloramphenicols ( catA1, catA2, catA3, catB3 ), and kanamycin ( aphA-3 ) were analyzed by PCR ( Kim et al, 2013 ). PCR primers for each antibiotic gene were performed in a final volume of 20 μL, containing 2 μL of DNA template, 10 μL of 2x Taq PLUS PCR Smart mix 1 (SolGent TM , Korea), 6 μL of sterile distilled water and 1 μL of each primer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolates that showed an antimicrobial resistance phenotype were screened for the presence of genes coding for resistance determinants. The genes associated with resistance to B-lactams ( blaTEM, blaSHV, blaOXA ), tetracyclines ( tetA, tetB, tetC, tetG ), chloramphenicols ( catA1, catA2, catA3, catB3 ), and kanamycin ( aphA-3 ) were analyzed by PCR ( Kim et al, 2013 ). PCR primers for each antibiotic gene were performed in a final volume of 20 μL, containing 2 μL of DNA template, 10 μL of 2x Taq PLUS PCR Smart mix 1 (SolGent TM , Korea), 6 μL of sterile distilled water and 1 μL of each primer.…”
Section: Methodsmentioning
confidence: 99%
“…There are numerous antibiotic resistant genes can be found in bacteria and environments. For example, β-lactam and penicillin resistant genes penA and blaTEM-1 ( Srinivasan et al, 2005 ; Zhang et al, 2009 ), chloramphenicol resistant genes cat I, cat II, cat III, cat IV, and floR ( Dang et al, 2007 , 2008 ), tetracycline resistant genes tatA, tatB, tatC, tatD, tatE, tatG, tatH, tatJ, tatY, tatZ , and many more ( Macauley et al, 2007 ; Zhang et al, 2009 ; Kim et al, 2013 ). These antibiotic resistant genes can be transfer among different bacteria via conjugation, transduction, or transformation ( Manjusha and Sarita, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning chloramphenicol, catA2 and catB3 resistance genes prevalent in psychrotrophic and mesophilic pseudomonads, respectively, are widespread in many bacteria (44), suggesting that the observed acquired resistance was due to horizontal gene transfer. On the other hand, the acquisition of the sulfamethoxazole (sulII) resistance gene, which is found predominantly on plasmids and associated with class 1 integrons (72,73), via horizontal gene transfer by pseudomonads was reported in enteric bacteria isolated from healthy food animals and humans (74,75), with sulII being the most prevalent gene in the absence of clinical selection pressure (76).…”
Section: Discussionmentioning
confidence: 99%
“…The microbiological breakpoints of most antibiotics tested were those defined by CLSI (35). Concerning betalactams (amoxicillin and ampicillin), kanamycin, streptomycin, and trimethoprim, we used the microbiological breakpoint proposed by CLSI (35) (43)(44)(45)(46)(47)(48)(49)(50) and using primers listed in Table S1 in the supplemental material. Efflux pumps mediating multiple antibiotic resistance also were included in this study (see Table S1), such as AcrA, AcrB, TolC, MexAB, MexCD, and MexXY (51,52).…”
Section: Methodsmentioning
confidence: 99%
“…Mostly, antibiotics resistance bacteria are found in soil sample of clinical and other hospital areas (Montelli and Levy, 1991). Many researchers have isolated and characterized the multiple drug resistance bacteria from different sources like edible snow crab (Kim et al, 2013), retail ground meat (White et al, 2001) and waste water (Pandey et al, 2011). In a similar study carried out by Chapin et al (2005), reported the existence of multidrug resistant bacteria in swine feeding materials.…”
Section: Introductionmentioning
confidence: 99%